Spatial Analysis of Rainfall Distribution in Serang City Using the Isohyet Method (Period 2020-2024) - Widyastuti, Irma; Ruhiat, Yayat; Suryana, Tresna Galih Sukma (SEARCH: Science Education Research Journal, 2026)
High and uneven rainfall distribution in Serang City frequently leads to hydrological problems, particularly flooding. The objective of this study is to analyze the spatial rainfall distribution in Serang City from 2020 to 2024 using the Isohyet method. Secondary rainfall The dataset was obtained from three rainfall observation stations: Class 1 Serang Meteorological Station, BPTPH Sawah Luhur Station, and BRMP Ciruas Station. Data normality was evaluated using the Kolmogorov–Smirnov test, which indicated that all datasets follow a normal distribution, where the lowest p-value was 0.010 and the highest KS statistic was 0.195. The analysis shows that the average monthly rainfall in Serang City is relatively high (>100 mm/month). The highest average rainfall was recorded at the Station Meteorologi Class 1 Serang (152.7 mm). The spatial mapping results based on the Isohyet approach show that rainfall distribution within the study area is relatively homogeneous. However, higher rainfall intensity is observed in the western region (Taktakan), influenced by orographic factors, while the northern region (Kasemen) records relatively lower rainfall intensity. These findings provide important information for understanding rainfall patterns and supporting hydrological management in Serang City. This study provides important baseline data for flood mitigation and urban drainage planning in Serang City.